A Novel Electrode With Electromagnetic Tip Tracking in Ultrasonography-Guided Radiofrequency Ablation. Issue 2 (February 2015) - Kang, Tae Wook; Lee, Min Woo; Choi, Seung Hee; Rhim, Hyunchul; Lim, Sanghyeok; Song, Kyoung Doo; Min, Ji Hye; Choi, Seo-youn; Lim, Hyo Keun; Yang, Jehoon
<x xml:space="preserve">Abstract</x> Objectives The objective of this study was to compare the targeting and ablation performance between a newly developed radiofrequency (RF) electrode embedded with an electromagnetic position sensor (EMPS) at the electrode tip and a conventional RF electrode. Materials and Methods The institutional animal care and use committee approved this study. The targeting of paint balls within phantoms was performed under ultrasonography guidance by 2 radiologists (beginner vs expert) with an "in-plane" and "out-of-plane" approaches using the new RF electrode and a conventional RF electrode (n = 20 for each method). To evaluate the targeting performance, the electrode placement time and the number of electrode pullbacks for redirection were compared between the 2 electrodes. The ablation performance was also compared by analyzing the ablation volumes in ex vivo bovine and in vivo porcine livers (n = 30 and n = 24, respectively) and the cellular viability of the ablation zone in in vivo specimens. Results In the phantom study, the RF electrode embedded with an EMPS showed a significantly shorter electrode placement time compared with the conventional RF electrode in both the in-plane and out-of-plane approaches by both radiologists (P < 0.05). The electrode pullback rate for both radiologists was lower in the new RF electrode than in the conventional RF electrode, but it did not reach statistical significance in the in-plane approach by the expert (P = 0.059). The ablation volumes analyzed with and without cellular viability in the ex vivo and in vivo studies were not significantly different between the 2 electrodes (P > 0.05). Conclusions The RF electrode embedded with an EMPS is faster than the conventional electrode in the electrode placement into the target lesions. The ablation performance is not significantly different between the 2 electrodes.